Determinants of E-Learning Adoption: Evidence from the Telecommunications Industry in Vietnam - BUI Tuyen Quang; NGUYEN Ngoc Minh; NGUYEN Phuong Mai (Foundations of Management)
As a response to the global digital transformation trend, e-learning has been chosen as a critical method in corporate training worldwide due to its efficiency and flexibility. However, the adoption of an e-learning system is limited in developing countries, particularly in enterprises. In such a context, this research examines factors affecting e-learning adoption in the Vietnamese telecommunications industry. A research model was developed based on the technology acceptance model (TAM), adding three antecedents: management support, technical support, and course quality. Using data collected from 248 employees working in the industry, we ran a structural equation modeling analysis to test seven proposed hypotheses. Our findings showed that perceived usefulness and perceived ease of use mediate the impact of management support, technical support, and course quality on e-learning adoption. Based on our findings, we proposed several suggestions to improve the e-learning system and promote the adoption of elearning in Vietnamese companies.